Development and validation of a fall health literacy scale for Chinese hospitals from the perspective of older adults - Miao, Tianxin; Chen, Ke; Han, Dianli; Zhao, Yingna; Duan, Liran; Zhang, Lan; Yao, Ying (Frontiers in Public Health, 2025)
Background and aimHealth literacy plays an important role in assessing patients’ ability to receive information about falls and in educating patients about their health. Understanding the level of fall health literacy of hospitalized older adults is essential for implementing fall prevention interventions, but tools for assessing the fall health literacy of hospitalized older patients are lacking. The aim of this study was to develop and validate an instrument for assessing fall health literacy among hospitalized older adults in China.MethodsThe Fall Health Literacy Scale for Hospitalized older adults was developed in two phases. In the first stage, dimensions and items were generated through a systematic literature review, semistructured interviews, and expert consultation. In the second phase, a cross-sectional study was conducted on 450 hospitalized older adults aged 60 years and above in two tertiary hospitals in Tianjin from March to July 2025 to test the reliability and validity of the items.ResultsThe scale comprises 30 items across five dimensions: cognition of fall information, transformation of fall information, implementation of fall information, knowledge of fall information, and personal attitudes and resource factors. This scale demonstrated excellent reliability, with a Cronbach’s α of 0.926, a split-half reliability of 0.884, and a test–retest reliability of 0.897. Furthermore, the results of the confirmatory factor analysis confirmed the good construct validity and reliability of the scale.ConclusionThe scale has good reliability and validity and is a tool for evaluating fall health literacy from the perspective of older adults; additionally, it provides a new perspective for reducing the incidence of falls in China.Clinical trial registrationhttps://www.chictr.org.cn/showprojEN.html?proj=273509.